Taimettumisalustassa olevien ravinteiden vaikutuksesta kurkun ja tomaatin sirkkataimien kehittymiseen - Suhonen, Irma (Agricultural and Food Science, 1972)
The effects of different nutrient solutions, the concentration of solution (0.1—0.48 %), nitrogen (0.26 g/l) and potassium (0.77 g/l) on seedling emergence and growth of pickling cucumber and tomato on coarse sand was studied. Experiments were made in a laboratory with temperature of 20—25° C and additional light of 780 lx or 2500—3000 lx, or in phytotrons. The after-effects of treatments were studied in greenhouse. The results show that a number of nutrient solutions accelerated seedling emergence, especially the Hoagland- and KNO3 -solutions and those which contained potassium or NO3—N. This phenomenon decreased with an increase in temperature. Compared to the treatment with distilled water, treatments with several nutrient solutions likewise accelerated seedling growth. The effect of potassium and NO3—N on growth was stimulatory, while urea and ammonium salt treatments could inhibit growth. The after-effects of treatments with 0.1—0.3 % KNO3 and 0.24 % Hoagland-solution were positive for four weeks.